Effects of Financial Planning, Savings Behavior, and Income Level on Retirement Readiness of Millenial Generation - Kaswoto, Junet; Rahayu, Ruci Arizanda; Marsiwi, Dwiati; Sudarmanto, Eko (Westscience Press, 2025)
This study examines the effect of financial planning, saving behavior, and income level on millennial retirement readiness. Employing a quantitative approach with 120 respondents, data were collected using a Likert scale (1–5) and analyzed through Structural Equation Modeling - Partial Least Squares (SEM-PLS). Results reveal that financial planning, saving behavior, and income level significantly influence retirement readiness, explaining 62% of its variance. These findings emphasize the interconnectedness of these factors and their implications for fostering retirement preparedness. Practical recommendations include enhancing financial literacy, promoting savings discipline, and addressing income disparities through policy and institutional interventions. The study contributes to the theoretical understanding of behavioral finance and offers actionable insights to improve millennials' financial security for retirement.